Susceptibility of potato cultivars to soft rot caused by Pectobacterium chrysanthemi - Lebecka, Renata; Michalak, Krystyna; Gurevich, Boris (MTT, 2007)
Pectobacterium chrysanthemi Ech (Burkholder et al. 1953) Brenner et al. 1973, Hauben et al. 1998, is the causal agent of two diseases of potato: blackleg and soft rot (1). Tuber rot of potato induced by Ech is a threat to potato cultivation in the tropics (2), but it is also found in the cooler climates (3). The diploid interspecific hybrid of Solanum spp., DG 88- 9, and 72 potato cultivars registered in Poland were evaluated for their susceptibility to Ech strain SCRI 4063 at two different temperatures, 30oC and 20oC. After incubation the width of decayed tissue was measured (in mm) in the widest part of vertically sliced tubers. All tubers of cultivars and the diploid clone were infected at a temperature 30oC, but not all were infected at a temperature 20oC. There were significant differences among cultivars in susceptibility to Ech. The statistical analysis of data (the width of decayed tissue at 30oC) obtained from 72 cultivars and one diploid clone has defined four groups (mean ± 95 % a confidential interval): I - 8 cultivars and the diploid clone poorly susceptible (9.0 ± 2.1), II - 17 cultivars moderately susceptible (13.2 ± 2.3), III - 36 cultivars susceptible (16.9 ± 2.1), IV - 11 cultivars strongly susceptible (19,9 ± 2,0). The cultivars, which were most susceptible at temperature 30oC, were more susceptible at temperature 20oC. The mean diameter of decayed tissue was 15.9 mm, with a range for individual cultivar from 7.7 mm to 22.0 mm. The diploid clone DG 88-9, used as resistant standard to tuber soft rot, showed the least infection with the mean value 7.2 mm. Tubers of 48 cultivars and the clone DG 88-9 did not show any symptoms of infection with Ech at a temperature 20oC. Tubers of 24 cultivars showed partial rotting, since symptoms of infection were observed for three to 10 inoculation sites out of 20 for each cultivar. It was observed that among 9 less infected cultivars at a temperature 30oC there was only one cultivar with symptoms of infection at a temperature 20oC. On the contrary, in the group of 11 cultivars highly infected cultivars at a temperature 30oC, 7 showed symptoms of infection at a temperature 20oC. The expression of potato resistance to bacteria Ech differs depending on the temperature. Temperature influences the bacterial growth rate as well as the wound-induced suberization and periderm formation in potato tubers. The wound healing occurs most rapidly at 25°C, and is delayed at 10 or 15°C, while a temperature of 35°C prevents the periderm formation and retards suberization (4). Our observations are in agreement with the statement of Perombelon et al. (5) that Ech could be a threat to potato in warmer countries but also in Central Europe due to warming climate.
Keywords: Ka; Pectobacterium chrysanthemi; potato; susceptibility; temperature